Projetos culturais : elementos mobilizadores para a vitalização da cultura e da democratização do espaço escolar da EMEB “Doutor Fábio Firmino Leite” - Pulquerio, Ivone Monteiro dos Reis (2006)
This research investigated the Cultural Projects implanted by the Municipal School of Education Basic "Doctor Fabio Firmino Leite", which were developed in the period from 2000 to 2004. These projects were centered in the cultural contribution and they had as a fort union element the strengthening of the participation and the democratization of the school space. The option for the already mentioned research object happened for we verify, along several years, that the democratic process in the school units of the municipal net of Cuiabá - MT was still linked, almost that exclusively, in the election for the school manager's choice, leaving of you consider it, also, as a factor that facilitates the access to the cultural goods, so essential in the educational process and to the citizen's formation. In the accomplishment of this work, we opted to use the qualitative research, once this has been making possible the several researchers a larger interaction among those than they investigate and the subjects that are involved in this process. We still used the following methodological contributions: bibliographical revision that subsidized the theoretical reflection on some essential themes, such as: the culture and your relationship with the education and the participation; the semistructured interviews, accomplished with the subject of the investigation, making possible that the same ones discoursed freely, in way to contribute for the enrichment of this work. It is necessary to emphasize so as to this research demonstrated as the cultural projects were key elements, collaborating in a significant way for the enlargement of the participation and, at the same time, making possible the participants that lived other forms of cultural manifestations. Like this, we can affirm that those existences contributed so that the school became a more pleased pedagogic space, where the development of the creativity, the development of the corporal expression, the solidarity and the cooperation were some of the main ingredients in the process of the school community's growth.